Effectiveness of Subsidies in Technology Adoption: A Case Study Involving Reverse Osmosis (RO) Membrane Technology - Nur Laili; Rendi Febrianda; Iin Surminah (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
Adoption of new technologies is a process that involves technological learning and penetration of new products into the market. Within the process of new technologies adoption, government usually intervened by providing incentives, in order to support the technology adoption to be succeed. This paper examines the effectiveness of incentives for the sustainability of reverse osmosis (RO) membrane technology adoption. The study conducted through single case study on SWRO installation in Mandangin Island, East Java, Indonesia. Results of case study indentify the existence of government incentive in the form of direct subsidies to decrease the price of clean water. Although successful in reducing the price of water, but effectiveness of the subsidy on the sustainability of SWRO is still low, which is operates only 30% in a year. Further analysis shows that these subsidies actually be counter-productive to the sustainability of SWRO installation.